(5y+9)(3y-4)=0

Simple and best practice solution for (5y+9)(3y-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5y+9)(3y-4)=0 equation:


Simplifying
(5y + 9)(3y + -4) = 0

Reorder the terms:
(9 + 5y)(3y + -4) = 0

Reorder the terms:
(9 + 5y)(-4 + 3y) = 0

Multiply (9 + 5y) * (-4 + 3y)
(9(-4 + 3y) + 5y * (-4 + 3y)) = 0
((-4 * 9 + 3y * 9) + 5y * (-4 + 3y)) = 0
((-36 + 27y) + 5y * (-4 + 3y)) = 0
(-36 + 27y + (-4 * 5y + 3y * 5y)) = 0
(-36 + 27y + (-20y + 15y2)) = 0

Combine like terms: 27y + -20y = 7y
(-36 + 7y + 15y2) = 0

Solving
-36 + 7y + 15y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(-9 + -5y)(4 + -3y) = 0

Subproblem 1

Set the factor '(-9 + -5y)' equal to zero and attempt to solve: Simplifying -9 + -5y = 0 Solving -9 + -5y = 0 Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5y = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -5y = 0 + 9 -5y = 0 + 9 Combine like terms: 0 + 9 = 9 -5y = 9 Divide each side by '-5'. y = -1.8 Simplifying y = -1.8

Subproblem 2

Set the factor '(4 + -3y)' equal to zero and attempt to solve: Simplifying 4 + -3y = 0 Solving 4 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3y = 0 + -4 -3y = 0 + -4 Combine like terms: 0 + -4 = -4 -3y = -4 Divide each side by '-3'. y = 1.333333333 Simplifying y = 1.333333333

Solution

y = {-1.8, 1.333333333}

See similar equations:

| 5x^2=2x-1 | | 5x^2-4x-3=0 | | 67-3x=24x+16 | | 4y^3+15y^2-4y=0 | | 12-x^2-2xy=0 | | 11-7x=75-21x | | -3x^2-12=4x | | 8(6+2p)=4-6p | | 11x^2+9=0 | | -8n(1-8n)-2(n+3)= | | 70-5x=8x+28 | | 2n+10=48 | | k+12=31 | | m-9=14 | | 8=2h-4 | | 3+4x=15x+7 | | 5y^2-16y=0 | | 6(1-3x)+7x(7-x)= | | (X+4)(x^2-4x+2)= | | 4x+50=9+10 | | -25=y-53 | | 0.75x=25 | | 4.5-p=1.75 | | 3x^3+6x^2*15x= | | 5x-11=7x+5 | | s-2=14 | | 71-2x=34x+15 | | p+21=-4 | | 420*k=140 | | 8x+11x= | | 5(7+2y/5)-2y=7 | | 3x-16=10x-68 |

Equations solver categories